Analisis Sistem Pengendalian Internal Atas Pembayaran Dana Pensiun Pada PT ASABRI (Persero) - Agustin, Kety Lulu; Endang Sri Apriani; Opu, Nur Vita (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
: Internal Control performed by PT ASABRI (Persero), the pension fund manager owned by BUMN, which will concentrate on the pension fund's actual payout. The study makes use of the following five COSO internal control framework components: information and communication, control activities, risk assessment, environmental control, and monitoring activities. PT ASABRI has an appropriate environment for the process of carrying out activities, has a system or application in accordance with activities, carries out both internal and external controls, and monitors and evaluates all activities that have been carried out by each related division, especially pension funds, according to the study's results, which were obtained using qualitative research methods